MOTIVASI MAHASISWI UNESA DALAM MENGIKUTI OLAHRAGA FUTSAL DI UKM UNIVERSITAS NEGERI SURABAYA - AYU PUSPA SARI, EKA (Jurnal Kesehatan Olahraga, 2016)
The background of this research is the sport become a necessity for everyone , both men and women , young and old, to maintain and improve the freshness and physical health. One sport that is very popular today and is favored by many futsal. Futsal is enough activity to attract many people either as a pastime or event kopetisi. Futsal become a popular sport among female students UNESA. This is evidenced by the emergence of UKM ( Student Activity Unit ) futsal Universitas Negeri Surabaya ( UNESA ) where to catch the spirit of the students is very high due to competition or tournaments are held at the national level, regions as well as between students. Formulation of the problem in this research is how high the level of motivation in following the UNESA student futsal in UKM Universitas Negeri Surabaya.This research was descriptive qualitative data collection using questionnaires contain a statement of the revelations that have been validated . Goal of research is the level of student motivation in following the sport of futsal Unesa in UKM Universitas Negeri Surabaya. The subjects were 30 students who are members of the UKM Universitas Negeri Surabaya.The results showed that the level of student motivation in following the sport of futsal Unesa in UKM State Universitas Negeri Surabaya seen from the intrinsic dimension is very high while the views of the extrinsic dimension is high . The overall level of student motivation in following Unesa futsal at the State Universitas Negeri Surabaya UKM is high .Keywords : Motivation , futsal